2021
DOI: 10.1038/s41398-021-01452-1
|View full text |Cite
|
Sign up to set email alerts
|

Altered levels of interleukins and neurotrophic growth factors in mood disorders and suicidality: an analysis from periphery to central nervous system

Abstract: Interleukins and neurotrophins levels are altered in the periphery of patients with major depression and suicidal behavior, however it is not clear if similar abnormalities occur in the central nervous system. Our objective was to examine the association of IL-6, IL-1β, BDNF, and GDNF levels between postmortem plasma, cerebrospinal fluid (CSF), and brain tissue in a heterogeneous diagnostic subject groups including normal controls, mood disorders only, mood disorders with AUD/SUD (alcohol abuse disorder, subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Arguments about the roles of tryptophan catabolites and cytokines in the CNS often center around the relationship between their systemic and central concentrations. Several studies of blood and CSF cytokine concentrations have shown parallel qualitative and quantitative changes, including those on TGF-β ( Liu et al, 2022 ) with one report of IL-6 levels in blood correlating highly with mood ( Gadad et al, 2021 ). The CSF: serum ratio of IL-6 levels was sufficiently consistent to act as a potential biomarker of intracranial aneurysms ( Kaminska et al, 2021 ), while increased levels of IL-6 in rat brain parenchyma occurred in parallel with plasma and CSF values and with the severity of traumatic brain injury ( Chatzipanteli et al, 2012 ).…”
Section: Limitations and Uncertainties: Concentrations And Correlationsmentioning
confidence: 97%
“…Arguments about the roles of tryptophan catabolites and cytokines in the CNS often center around the relationship between their systemic and central concentrations. Several studies of blood and CSF cytokine concentrations have shown parallel qualitative and quantitative changes, including those on TGF-β ( Liu et al, 2022 ) with one report of IL-6 levels in blood correlating highly with mood ( Gadad et al, 2021 ). The CSF: serum ratio of IL-6 levels was sufficiently consistent to act as a potential biomarker of intracranial aneurysms ( Kaminska et al, 2021 ), while increased levels of IL-6 in rat brain parenchyma occurred in parallel with plasma and CSF values and with the severity of traumatic brain injury ( Chatzipanteli et al, 2012 ).…”
Section: Limitations and Uncertainties: Concentrations And Correlationsmentioning
confidence: 97%
“…Another one found a weak hippocampus-serum correlation for pro-BDNF but not for BDNF or the other two brain areas [ 48 ]. The third one also did not find a correlation for BDNF, but found a trend for GDNF [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Large compounds, such as brain-specific proteins, do not usually cross the BBB; for some of them, the permeability is still unknown. For example, in humans, it is not consensual yet whether brain-derived neurotrophic factor (BDNF) easily permeates the BBB (see references in [ 6 ]), and, therefore, whether blood BDNF may reflect central BDNF.…”
Section: Introductionmentioning
confidence: 99%
“…BDNF is able to cross the blood-brain barrier and its plasma levels reflect the central nervous system levels ( 52 ). In addition, studies suggest that the mature form of BDNF and its precursor pro-BDNF could have opposite functions on neural plasticity: while mature BDNF promotes neuronal survival and growth, pro-BDNF induces neuron apoptosis ( 53 ).…”
Section: Discussionmentioning
confidence: 99%